Mucosal immunity and illness incidence in elite rugby union players across a season - Cunniffe, B.; Griffith, H.; Proctor, W.; Davies, B.; Baker, J. S.; Jones, K. P. (Medicine & Science in Sports & Exercise, 2011)
Purpose: To examine the relationship between upper respiratory illness (URI) incidence with changes in mucosal immunity (saliva immunoglobulin A (s-IgA) and saliva lysozyme (s-Lys)) and training load (TL) in a squad of elite rugby union players.